Revealing the Translator as a Political and Cultural Agent: An Archival Research on Sabahattin Ali’s Translational Practices - Malaymar, Deniz (TTR, 2021)
Sabahattin Ali (1907-1948) is a prominent figure in Turkish literary history. He was not only a renowned writer and journalist but also a notable translator. He was one of the founding members of the state-sponsored Translation Bureau (1940-1966). He translated many books, short stories, and articles from German into Turkish, both within and outside the Bureau. In the 1930s and 1940s, however, his socialist and Marxist convictions came to the forefront. He was imprisoned several times for disseminating socialist and communist propaganda. The periodicals he published and the works he wrote were banned and confiscated by the government. Despite the persecution he suffered, Ali held to his belief that socialism (and in particular, Marxism) was the only path toward national development and the only solution to the social and economic problems of the country. With this motivation in mind, he aimed to disseminate leftist ideas in the Turkish culture by way of translation. Even though Ali was an effective and productive translator, his translation-related activities have not attracted adequate attention among researchers. This study, therefore, aims to reinstate Sabahattin Ali as a translator, as well as a political and cultural agent. By referring to the concepts of “culture repertoire,” “resistance,” and “culture planning” proposed by Itamar Even-Zohar (1997, 2002), it explores Ali’s resistance to the culture planning project of the single-party era of 1923-1945 and his attempts to develop an alternative repertoire of leftist works through translation. To give a wider picture of his ideologically motivated translational activities, certain primary sources available on Sabahattin Ali are analyzed, such as his published correspondence and the memoirs of his close circle of family and friends, which testify to his translation-related practices, to his political views and endeavours, as well as to the socio-political climate of the 1930s and 1940s in Turkey.